Implementation of MMI structure for optical device using polymer material - Ahmad Wahiddin, Farah Waheeda (2007)
Multimode interference (MMI) devices have been extensively studied and are of considerable interest as key optical components in photonic integrated circuit (PIC). The principle of the MMI devices is based on destructive/constructive interferences occurring in the MMI area with a large number of multimodes. Because of its unique properties, such as low insertion loss, large optical bandwidth, compactness, low crosstalk and excellent fabrication tolerances, the MMI devices has many potential applications such as couplers, splitters, combiners, filters and routers. Compared with silica, recently, polymeric material has lately attracted considerable attention for various waveguide devices, such as optical switches and variable optical attenuators, especially for its simple fabrication process.